Facebook's shared articles on HPV vaccination: analysis of persuasive strategies - Ashley Hedrick McKenzie; Elaine Avshman; Ross Shegog; Lara S. Savas; L. Aubree Shay (BMC, 2024)
Abstract Background The current study analyzed articles shared on Facebook between 2019 and 2021 that discuss the HPV vaccine. Results address a gap in knowledge about the persuasive strategies used in HPV vaccine discourse on Facebook. Methods Using Buzzsumo.com, we collected 138 articles, shared on Facebook between 2019 and 2021, with the highest "engagement scores," or total number of reactions, comments, and shares. Using a content analysis methodology, three independent coders were trained in using the study codebook, achieved acceptable inter-rater reliability (Krippendorf's alpha = 0.811), and coded each article in Atlas.ti. Results Seventy-two articles had a positive valence toward the HPV vaccine, 48 had a negative valence, and 18 were mixed-valence or neutral. Pro-vaccine articles presented a variety of evidence types in support of benefits of HPV vaccination. Pro-vaccine articles primarily originated from national and local news sources. Anti-vaccine articles combined presentation of evidence with persuasive arguments and strategies, such as mistrust of institutions, fear appeals, ideological appeals, presenting a high number of arguments or detail, and minimizing the severity of HPV. Three sources were responsible for producing 62.5% of all anti-vaccine articles in the dataset. Mixed-valence or neutral articles mixed cancer prevention discourse with ideological appeals about protecting parental rights, and were mostly produced by local news outlets. Conclusion The results of this study can help health communicators anticipate the types of discourses that vaccine-hesitant parents may have encountered online. Implications and suggestions for practice are discussed.